Towards more efficient nitrogen removal and phosphorus recovery from digestion effluent: Latest developments in the anammox-based process from the application perspective. (March 2020) - Guo, Yan; Chen, Yujie; Webeck, Elizabeth; Li, Yu-You
Graphical abstract: Highlights: The latest development of anammox-based processes was summarized. Nitritation is the rate-limiting step in the anammox-based process application. One-stage anammox process has obvious advantages over the two-stage anammox process. The HAP crystallization and denitratation bring novel ideas in anammox research. A simultaneous nitrogen removal and phosphorus recovery process were proposed. Abstract: Over the past forty years, anammox-based processes have been extensively researched and applied to some extent. However, some of the long-standing problems present serious impediments to wide application of these processes, and knowledge gap between lab-scale research and full-scale operations is still considerable. In recent years, anammox-based research has developed rapidly and some emerging concepts have been proposed. The focus of this review is on the critical problems facing actual application of anammox processes. The latest developments in anammox-based processes are summarized, and particular consideration is given to the following aspects: (1) the evolution of the chemical stoichiometry of anammox reaction; (2) the status of several main anammox-based processes; (3) the critical problems and countermeasures; (4) the emerging anammox-based processes; and (5) the suggested optimal process integrating partial nitritation, anammox, hydroxyapatite crystallization and denitratation for digestion effluent treatment towards more efficient nitrogen removal and phosphorus recovery in the future.